Issues of ensuring the information security of the child in the digital space of the Republic of Kazakhstan - Akimzhanova М.T.; Ilyassova, G.A. (Bulletin of the Karaganda University “Law Series”, 2023)
The rapid development of social resources of Internet technologies has led to a sharp increase in the number of users of all ages, among them children, who are consumers of various, including destructive information. Today, modern global trends signal the emergence of new formats of threats and online risks. Children are active users of the global Internet, and most of them are unaware of the danger that information in the virtual space may contain. To be more precise, it is the propaganda of the consumption of alcohol, drugs, violence and cruelty, aggressive and suicidal behavior, etc. The authors identified and gave characteristics of information threats, such as cyberbullying, considered the problems of child suicides that are committed through “death groups” in social networks. We have presented action plans on the part of the state, and also highlighted preventive measures to ensure the information security of the child in the global information space. The article provides examples of solving the problem of information security in the Republic of Kazakhstan and other countries based on a review of publications on this issue, as well as regulatory legal acts of the Republic of Kazakhstan and foreign countries. We have revealed the issues of the need for further study of the problem and the development of preventive measures aimed at preventing the occurrence of information threats and online risks. In order to prevent such offenses, conclusions are drawn about the expediency of developing measures of both social and legal orientation. The results of the study were possible measures proposed by the authors regarding the improvement of the system of legal provision of information security of children in the Republic of Kazakhstan.